A clinical score for predicting complications following breast reduction - Rami Ali Eleiba; Bassem Elfeki; Khalid Ahmed Ismail; Safwat Adel Hegazy (Journal of the Pakistan Medical Association, 2023)
Objective: To establish a clinical score for morbidity prediction based on patient-related risk factors after breast reduction surgery. Method: The retrospective study was conducted at the Department of Plastic and Reconstructive Surgery, Kafrelsheikh University Hospital, Egypt, and comprised data of female patients with bilateral macromastia who underwent breast reduction, using the inferior pedicle inverted T technique between February 2019 and June 2020. After data retrieval, risk factors and complications were documented and related to the patients’ risk factors Data was analysed using SPSS 20. Results: Of the 30 cases, 20(66.7%) were aged ≧35 years, 16(53.3%) had body mass index ≧37kg/m2 and 27(90%) were non-smokers. The mean preoperative haemoglobin level was 12.15±1.115g/dL and the mean weight of tissue resected on both sides was 2074.17±696.12gm. Factors significantly associated with complications included smoking, suprasternal notch to nipple distance ≧38cm, haemoglobin <12.5g/dL, the weight of excised tissue ≧2000gm and a positive family history of macromastia. The total score of the morbidity prediction scale ranged 2-190, with the best cut-off value being ≧93. The scale had 100% sensitivity, specificity, positive predictive value, negative predictive value and 100 percent accuracy. Conclusion: Ability to predict postoperative surgical-site morbidity may optimise safety as well as outcome after reduction mammaplasty. Keywords: Gigantomastia, Nipples, Mammaplasty, Macromastia, Morbidity, Pedicle